2004
DOI: 10.1002/chem.200305738
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Electronic Structure of a Novel [Ni‘S4’Fe2(CO)6] Radical Cluster: Implications for the Active Site of the [NiFe] Hydrogenases

Abstract: A novel [NiS4Fe2(CO)6]cluster (1: 'S(4)'=(CH(3)C(6)H(3)S(2))(2)(CH(2))(3)) has been synthesised, structurally characterised and has been shown to undergo a chemically reversible reduction process at -1.31 V versus Fc(+)/Fc to generate the EPR-active monoanion 1(-). Multifrequency Q-, X- and S-band EPR spectra of (61)Ni-enriched 1(-) show a well-resolved quartet hyperfine splitting in the low-field region due to the interaction with a single (61)Ni (I=3/2) nucleus. Simulations of the EPR spectra require the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 86 publications
7
42
0
Order By: Relevance
“…Similar results were also found by the group of Schröder with a bisthiolate-bisthioether ligand [82]. For the NiFe 2 complex 21 with this latter ligand, the resulting species obtained after one-electron reduction showed ESR hyperfi ne coupling when enriched with 61 Ni, and an average shift of 70 cm Ϫ1 for the CO bands in the IR spectrum.…”
Section: 19supporting
confidence: 75%
“…Similar results were also found by the group of Schröder with a bisthiolate-bisthioether ligand [82]. For the NiFe 2 complex 21 with this latter ligand, the resulting species obtained after one-electron reduction showed ESR hyperfi ne coupling when enriched with 61 Ni, and an average shift of 70 cm Ϫ1 for the CO bands in the IR spectrum.…”
Section: 19supporting
confidence: 75%
“…[16][17][18][19]34 Despite the hundreds of structural models developed to date, few have been reported to show electrocatalytic activity related to proton reduction or hydrogen oxidation. While upwards of 50 structural mimics of [NiFe] hydrogenases have been reported, initially only biomimetic complexes that deviated significantly from the enzyme structure displayed any electrocatalytic behavior, including a trinuclear {Ni'S 2 'Fe 2 } system [35][36] and a few Ni-Ru complexes [37][38][39][40][41][42] …”
Section: Biomimetic Hydrogenase Complexesmentioning
confidence: 99%
“…[31] On the other hand, a team of chemists in the UK including Schröder found that complex [(CO) 6 12 (Figure 9). [32] Similarly, Sellmann and co-workers used Ni('S 4 ') {21; 'S 4 ' = 1,2-bis(2-mercaptophenylthio)ethane} and Ni('S 4 C 3 Me 2 ') {22; 'S 4 C 3 Me 2 ' = 1,3-bis(2-mercaptophenylthio)-2,2-dimethylpropane} as precursors for the analogous Fe 2 Ni complexes [(CO) 6 Fe 2 ('S 4 ')Ni] (30) and [(CO) 6 Fe 2 ('S 4 C 3 Me 2 ')Ni] (31), respectively ( Figure 9). [33] The Ni-Fe [2.4789(9)-2.5038 (4) [25] Chemical reduction of 29 with Cp 2 Co (or electrochemical reduction of 29) leads to the formation of [29] -, which is EPR active and shows an interaction between the unpaired electron and the nickel nucleus upon 61 Ni (I = 3/2) enrichment.…”
Section: Precursors Of the [Ni(n 2 S 3 )] And [(Dppe)ni(pdt)] {Dppe =mentioning
confidence: 97%
“…Schröder and co-workers used trinuclear Fe 2 Ni complex 29 [32] as a catalyst for the electrochemical reduction of H + . [60] than 1 h. On the basis of DFT calculations and spectroscopic evidence, the SOMO of [29] -containing the unpaired electron was suggested to be delocalized over the Ni and the two Fe atoms, implicating metal-based protonation during catalysis.…”
Section: One-pot Self-assembly Reactionsmentioning
confidence: 99%